2021
DOI: 10.1039/d0cp05918h
|View full text |Cite
|
Sign up to set email alerts
|

Long-lived electrets and lack of ferroelectricity in methylammonium lead bromide CH3NH3PbBr3 ferroelastic single crystals

Abstract: Accumulation of CH3NH3+ and Br− ionic species at the ferroelastic domain boundaries creates a polar electret state in the hybrid perovskite CH3NH3PbBr3 that mimics a ferroelectric P(E) hysteresis loop.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 88 publications
2
6
0
Order By: Relevance
“…Our conclusion agrees with several X-ray diffraction experiments ,, and with more recent reports of a lack of ferroelectric switching in the orthorhombic phase. It has been suggested that there may exist local minima slightly higher in energy than the Pnma structure differing from it by small relative rotations and displacements of the MA ions . While these were ruled out in our 0 K optimization studies, we considered their possible occurrence at higher temperatures through our 0 GPa AIMD simulations at 40, 180, and 300 K (see SI).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…Our conclusion agrees with several X-ray diffraction experiments ,, and with more recent reports of a lack of ferroelectric switching in the orthorhombic phase. It has been suggested that there may exist local minima slightly higher in energy than the Pnma structure differing from it by small relative rotations and displacements of the MA ions . While these were ruled out in our 0 K optimization studies, we considered their possible occurrence at higher temperatures through our 0 GPa AIMD simulations at 40, 180, and 300 K (see SI).…”
Section: Resultssupporting
confidence: 93%
“…In particular, 96-atom supercells used previously along with the Γ-point only approximation led to a spurious polar minimum in MAPbBr 3 (see SI). A unimodal distribution of the dihedral angle θ 12 between MA 1 and 2 under the v or w group confirms the absence of any local (intermediate polar) energy minima close to the nonferroelectric/antipolar arrangement (θ 12 = 180°) (see Figure S4) and is in agreement with observations made in a recent MD study by Bokdam et al The occurrence of such intermediate-polar minima at 0 K in previous studies is an artifact of fixed cell optimizations, a constraint not imposed by our variable-cell simulations (see SI). While a polar arrangement of MA (θ 12 = 0°) with slightly higher energy (≈2 meV/atom) as the antipolar one is also possible (see SI), it was not accessed in the 40 K simulations.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…That is, PL modulation can be in-phase (for sinewave V initial > 0, Figure 2b) or antiphase (for π-shifted sinewave V initial < 0, Figure 2c) with the oscillating field, which appears to indicate a rapidly formed internal field in the nanowires, opposing the direction of the very initial external Efield applied. Furthermore, once the response direction is set, it cannot be flipped (on a measured time scale of several weeks), even when applying opposite DC fields of a higher magnitude (up to 2 × 10 7 V/m), meaning the system does not behave as a ferroelectric, 12 but rather resembles an electret, 13 a material exhibiting a dynamically stable electric dipole. 14 We note that more than 80% of the 54 measured nanowires showed PL modulation above the noise level, all responding asymmetrically, out of which about 70% followed the direction of the initial external field.…”
Section: Resultsmentioning
confidence: 99%